Effect of the Molecular Polarizability of SAMs on the Work Function Modification of Gold: Closed‐ versus Open‐Shell Donor–Acceptor SAMs. Issue 5 (17th October 2018) - Diez‐Cabanes, Valentin; Morales, Dayana C.; Souto, Manuel; Paradinas, Markos; Delchiaro, Francesca; Painelli, Anna; Ocal, Carmen; Cornil, David; Cornil, Jérôme; Veciana, Jaume; Ratera, Imma
Abstract: Charge injection barriers at metal/organic interfaces can be tuned by modifying the work function of metallic electrodes using self‐assembled monolayers (SAMs) of polar molecules. An interesting example of polar molecules is offered by donor–acceptor (D–A) dyads based on ferrocene (Fc) as electron‐donor unit and either a polychlorotriphenylmethyl radical or a polychlorotriphenylmethane as electron‐acceptor units, connected by a π‐conjugated vinylene bridge. The D–A radical exhibits high chemical and thermal stability and presents different electronic, optical, and magnetic properties with respect to the closed‐shell form. The magnitude of the shift in the charge injection barriers for these two D–A systems is estimated by means of surface potential measurements performed by Kelvin probe force microscopy. The experimental data are compared with density functional theory calculations, which evidence the importance of the molecular dipole moments and polarizabilities to understand the experimental values. In order to achieve high work function shifts of metals upon SAM formation, the molecules forming the SAM have to exhibit both a high permanent dipole moment and a low polarizability along the direction normal to the substrate. In presence of polarizable molecules, the work function shifts can be enhanced by reducing the intermolecular interactions; by using mixed SAMs with active molecules embedded into a passive matrix. Abstract : A modification in the Au work function is observed upon absorption of donor–acceptor closed‐ and open‐shell self‐assembled monolayers (SAMs). Theoretical calculations provide an understanding of the role played by the molecular polarizability and depolarization effects in the magnitude of these work function shifts providing practical hints to attain high work function shifts of metals upon SAM formation.